Life cycle assessment in the building design process – A systematic literature review - Roberts, Matthew; Allen, Stephen; Coley, David (Building and environment, 2020)
Buildings contribute a significant portion of global greenhouse gas emissions and have the potential for large-scale impact reductions. Reducing the whole-life impacts of buildings is critical for creating a net-zero carbon built environment. For this to be achieved, the whole-life carbon impacts of design decisions must be considered during the building design process. A systematic review of academic literature was conducted to assess how life cycle assessment (LCA) is incorporated at various stages of the building design process, and what improvements are needed to support net-zero carbon design. The review compiled 274 papers that were published up to the end of 2019, of which 108 were subject to detailed review following screening. The review found that LCA is generally used late in the design process, when it is too late to greatly influence the design. Incorporating LCA with either building information modelling or life cycle costing is seen to have the same challenges as undertaking a traditional LCA. Parametric methods show promise for design development, but tools and algorithms require further verification and regionalisation to be implemented throughout industry. The use of benchmarks, target values and other pre-populated information can be used to incorporate life-cycle thinking without the need to undertake a detailed LCA. The review has demonstrated that LCA continues to face barriers, in both methods and practice, preventing its ability to guide early-stage design decisions and have a large impact on the environmental performance of buildings. •Life cycle thinking is needed to produce a net-zero built environment.•Reactive methods are predominantly used to conduct environmental assessment.•Reactive methods assess building designs after completion.•Proactive methods can guide decisions during early-stage design.•Proactive methods are a viable means of reducing whole-life impacts in buildings.